DETERMINANTS OF CAPITAL STRUCTURE AND EFFECTIVE TAX RATE AS MODERATION VARIABLES - Mubarok, Ahmad Zakki; Sunaryo, Dede; Pangesti, Faralia Abdi; Febrianto, Hendra Galuh; Haq, Saiful (Univesitas Muhammadiyah Tangerang, 2024)
The aim of this research is to determine the influence of asset structure, profitability, business risk and company size on capital structure with the effective tax rate as a moderating variable in food and beverage companies listed on the Indonesia Stock Exchange (BEI). The research time period used was 5 years, namely the 2018-2022 period. The sampling technique uses purposive sampling technique. Based on the predetermined criteria, 24 companies were obtained that met the criteria. The type of data used is secondary data obtained from the Indonesian Stock Exchange website. The analytical method used is panel data regression analysis. The research results show that fixed asset structure has a positive effect on capital structure, profitability has a negative effect on capital structure, while business risk and company size have no effect on capital structure. Effective tax rate is able to moderate the positive influence of asset structure on capital structure, but cannot moderate the influence of profitability, business risk and company size on capital structure. Asset structure, profitability, business risk and company size together influence the capital structure.